Work, family and values in four Latin-American countries - Ruiz-Gutierrez, Jaime A. (Animo Repository, 2012)
Purpose - The purpose of this paper is to explore work-family conflict antecedents in four Latin American countries by studying whether marital status and number of children impacted values. Design/methodology/approach - A convenience sample of 3,529 working adults in major cities in Argentina (n = 1,198), Brazil (n = 186), Colombia (n = 989) and Mexico (n = 1,156) were surveyed using the Rokeach Value Survey. Findings - There were statistically significant differences in values depending on marital status for the terminal values an exciting life, national security, and pleasure, and also differences between respondents depending on having or not, and number of children for the terminal values pleasure, national security, and for the instrumental values logical, and polite. Originality/value - This study fills a research gap, as no previously published studies have explored whether marital status or number of children impact values. © Springer-Verlag Berlin Heidelberg 2013.